Erythrodermic tinea corporis with iatrogenic Cushing’s syndrome. - Kapadia, F.; Naskar, S.; Chikhalkar , S.; Kharkar, V. (European Journal of Pediatric Dermatology, 2021)
Dermatophytosis is a rampantly emerging challenge in the developing countries. However, erythroderma secondary to tinea corporis is rare. It is strange how alongside the prevailing corticophobia there are, albeit exceptionally, cases of excessive administration of topical corticosteroids, as happened in the ’70s in the developed countries. Inadvertent abuse of topical corticosteroids (2, 3) leads to not only a change in the morphology of the lesions but also to uncontrolled replication of the fungi making the disease widespread, chronic, and recurrent in nature. Moreover, the inappropriate use of corticosteroid preparations can cause both local and systemic (1, 4, 5) adverse effects related to any one of the variables as follows: quantity per application, frequency of application, duration of treatment, potency, vehicle used and site of application. Children are especially more prone to the systemic adverse effects of these drugs because their skin has poorly developed barrier function and mainly because of a higher skin surface area/weight ratio compared to adults. The abuse of topical corticosteroids in various combinations and very often of high potency has become one of the most challenging yet overlooked menace in the practise of dermatology in India. A multifaceted approach involving medical, administrative and judicial systems will go a long way in curbing the menace. Educating the public via mass media and continuing medical education for practioners are also direly needed to break the cycle of mismanagement and the subsequent damage inflicted by this once easily curable skin infection.